1990
DOI: 10.1007/bf02540650
|View full text |Cite
|
Sign up to set email alerts
|

Membrane applications and research in the edible oil industry: An assessment

Abstract: Commercial sources of edible oils and fats include oil‐seeds, fruit pulps, animals and fish. Oilseeds processing typically consists of the following steps: i) seed preparation; ii) solvent extraction of flakes and/or extruded collets; iii) desolventization of the meal;iv) recovery of solvent by distillation; and v) degumming, refining, bleaching, and deodorizing of the crude oil. The process consumes large amounts of energy—in the forms of electricity, natural gas and fuel oils—to heat and cool the oil between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 14 publications
1
40
0
3
Order By: Relevance
“…The applications usually improve the process of production, such as shortening the process, decreasing the temperature, leading the reaction to a specific direction, etc., and have many advantages over other separation techniques (2). Most investigations of membrane applications in lipid separation have been focused on the recovery of solvent from micella, separation in degumming, refining and bleaching, condensate return, catalyst recovery (2)(3)(4), hydrolyses of oils and fats (5)(6)(7)(8), or the syntheses of acylglycerols in two-phase membrane reactors (9). The direct separation of free fatty acids (FFA) from triacylglycerols was also investigated in a membrane reactor (10) and a review on enzymatic membrane reactors has been published (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The applications usually improve the process of production, such as shortening the process, decreasing the temperature, leading the reaction to a specific direction, etc., and have many advantages over other separation techniques (2). Most investigations of membrane applications in lipid separation have been focused on the recovery of solvent from micella, separation in degumming, refining and bleaching, condensate return, catalyst recovery (2)(3)(4), hydrolyses of oils and fats (5)(6)(7)(8), or the syntheses of acylglycerols in two-phase membrane reactors (9). The direct separation of free fatty acids (FFA) from triacylglycerols was also investigated in a membrane reactor (10) and a review on enzymatic membrane reactors has been published (11).…”
mentioning
confidence: 99%
“…When the permeation flux of PUFA is much lower than that of MCFA (J PUFA << J MCFA ), MCFA is removed from the reaction environment and the equilibrium is pushed toward the SL side. According to the fundamental theory (1), the flux of FFA can be written as: [3] where C a and C b are the concentrations of FFA in Chamber A and B, respectively; k is a constant, which is related to the overall mass transfer coefficient and reactor configuration; and J FFA is the flux of FFA. There are three cases for Equation 3 to be considered.…”
mentioning
confidence: 99%
“…vegetable oil refining, degumming process, deacidification and solvent recovery. In this regard, only a few research reports are available in open literature [1][2][3][4][5][6]. Ngyuen et al [7] observed that solvents (viz.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are looking at membrane technology as an alternate process to the conventional refining of edible oils (Koseoglu andEngelgau, 1990, Snape andNalajima, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The membrane process is remarkably simple, offering many advantages over conventional processes, namely, low energy consumption, ambient temperature operation, and retention of nutrients and other desirable components (Koseoglu and Engelgau, 1990). Recently, a refining process of vegetable oils using a hydrophobic nonporous denser membrane has been created.…”
Section: Introductionmentioning
confidence: 99%